2012
DOI: 10.1158/1538-7445.am2012-3278
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 3278: Sustained multilocular adipose tissue phenotype in adult Brca1 mutant mouse mammary gland is correlated with an increase in BMP7

Abstract: A major challenge to breast cancer research is the identification of alterations in the architecture and composition of the breast that are associated with breast cancer progression. Mammary epithelial cells are surrounded by an environment of supporting cell types, including the extracellular matrix, fibroblasts, and adipose tissue. Recent studies have demonstrated that this surrounding environment is an important regulator of tumor cell fate. The aim of the present investigation was to characterize the mamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The observation that Ccn6 fl/fl ;MMTV‐Cre mice mammary glands showed delayed age‐related involution with residual terminal end buds and brown fat after 8 months of age may shed light into preneoplastic progression. Defective age‐related involution with persistent brown adipose has been reported in mammary glands from adult Brca1 mutant mice prior to development of poorly differentiated carcinomas (Jones et al 2011). Recent studies in human tissues showed that defective age‐related lobular involution is significantly associated with increased risk for breast cancer (Milanese et al 2006; Radisky and Hartmann 2009).…”
Section: Ccn6 Emerges As a Tumor Suppressor For High‐grade Spindle Me...mentioning
confidence: 97%
“…The observation that Ccn6 fl/fl ;MMTV‐Cre mice mammary glands showed delayed age‐related involution with residual terminal end buds and brown fat after 8 months of age may shed light into preneoplastic progression. Defective age‐related involution with persistent brown adipose has been reported in mammary glands from adult Brca1 mutant mice prior to development of poorly differentiated carcinomas (Jones et al 2011). Recent studies in human tissues showed that defective age‐related lobular involution is significantly associated with increased risk for breast cancer (Milanese et al 2006; Radisky and Hartmann 2009).…”
Section: Ccn6 Emerges As a Tumor Suppressor For High‐grade Spindle Me...mentioning
confidence: 97%